The Impact of Teaching Effectiveness and Student Motivation in Learning English on English Achievement among University Students - Simanungkalit, Ate Gueen (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Several factors were positively or negatively correlated with student academic achievements, such as teaching effectiveness and student motivation. However, numerous variables of teaching effectiveness and student motivation have yet to be identified in a more specific context, and thus, it is deemed necessary to find out whether or not the teaching effectiveness used and the motivation considered is to be influential in academic achievement. This descriptive and quantitative study was intended to find out English teaching effectiveness, student motivation in learning English, and English achievement among the students at a selected private university, particularly differences between English major students and non-English major students on their perception of teaching effectiveness and motivation in learning English, and the impact of both teaching effectiveness and student motivation in learning English on English achievement. Two questionnaires were used to obtain data: The Teaching Effectiveness developed by Rondonuwu (2006) and Student Motivation in Learning English developed by Clement, Dornyei, and Noels (1994). There were 64 respondents who participated in this study by returning the filled-out questionnaires through emails. The results showed: (a) high level of teaching effectiveness; (b) high level of student motivation in English learning; (c) insignificant difference between English major students and non-English major students perception of teaching effectiveness, motivation in learning English, and English achievement; and (d) significant impact of both students perception of teaching effectiveness and student motivation in learning English on student English achievement. Keywords : academic achievement, teaching effectiveness, English major, students